Global Functioning of COPD Patients With and Without Functional Balance Impairment: An Exploratory Analysis Based on the ICF Framework. (14th April 2015) - Cruz, Joana; Marques, Alda; Jácome, Cristina; Gabriel, Raquel; Figueiredo, Daniela
Abstract Balance impairment is a common manifestation in older people with COPD and may contribute to overall functional decline; however, the relationship between balance and global functioning has not been studied. This study aimed to explore the global functioning of COPD patients with and without functional balance impairment. Functional balance was assessed with the Timed Up-and-Go (TUG) test and global functioning with the Comprehensive ICF Core Set for Obstructive Pulmonary Diseases. Participants (n = 134) were divided in 2 groups according to their performance in TUG (with and without balance impairment) and the ICF Core Set results were compared between groups. Fifty-four (40.3%) participants had functional balance impairment. The groups presented a similar extent of problems in several categories of the ICF components. However, participants with balance impairment were more severely affected (p < 0.05) in energy, pain, respiratory system, weight maintenance, exercise tolerance, neuromusculoskeletal and movement-related functions, and structure of head and neck. They also presented a significantly worse performance in handling psychological demands and activities related to mobility, self-care, domestic, community and social life, and a more negative perception of Environmental factors related to products and technology of buildings for private use and social support services (p < 0.05). Patients with functional balance impairment have more functional problems and are more severely restricted in daily life than patients without compromised balance. Understanding the relationship between balance control and global functioning will contribute to guide interventions aimed at maintaining functioning and minimizing disability.